Kandungan logam berat besi (Fe) dan timbal (Pb) pada air lindi TPA Putri Cempo, Surakarta - Rachmawati, Siti; Bernadetta, Patricia; Mardiyanto, Muhammad Bondan; Fil’ardiani, Nida Ulhaq; Khoirunnisa, Sofiyana; Arta, Yunia Putri Annisa (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Leachate is water from waste seepage that contains heavy metals; therefore, it has the potential to pollute soil, groundwater, and surface water and is dangerous for human health. The content of heavy metals Fe and Pb are important indicators that have an impact on water and soil. Landfill as a place for storing urban waste produces leachate, which is indicated to be contaminated with metal compounds, such as Fe and Pb. The aim of the research is to analyze heavy metals iron (Fe) and lead (Pb) compounds in leachate at the Putri Cempo landfill, Surakarta. This research was located at the Putri Cempo landfill, Surakarta, with leachate water samples taken in the ditch around the landfill. Data analysis used SSA (Atomic Absorption Spectrophotometry). The heavy metal Fe in the Putri Cempo landfill leachate has a leachate content of 0.62 mg/L, while the heavy metal Pb has a leachate content of 0.07 mg/L. The content of heavy metal compounds Fe and Pb still complies with the quality standards (Ministry of Environment Regulation Number 5 of 2014). Efforts that can be made to minimize the environmental impact on leachate include phytoremediation methods, adsorption methods, as well as anaerobic, aerobic, and denitrification methods.